Something's gotta give - Block, Bruce A.; Meyers, Nancy; Nicholson, Jack.; Keaton, Diane; Reeves, Keanu; McDormand, Frances; Peet, Amanda, 1972-; Favreau, Jon.; Glaser, Paul Michael; Ballhaus, Michael, 1935-; Hutshing, Joe.; Zimmer, Hans.; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2004)
Harry Sanborn is a perennial playboy with the libido of a much younger man. During what was to be a romantic weekend with his current infatuation, Marin, at her mother's Hampton beach house, Harry develops chest pains. He winds up being nursed by Marin's reluctant mother, Erica. When Harry hesitates to act on his feelings for Erica, Harry's thirtysomething doctor steps in and starts to pursue Erica. Harry, who has always had the world on a string, finds his life is now unraveling.
DVD, Region 1, widescreen (1.85:1) presentation; 5.1 Dolby Digital, DTS, SDDS.
English or dubbed French dialogue, French or Spanish subtitles; closed-captioned.
Jack Nicholson, Diane Keaton, Keanu Reeves, Frances McDormand, Amanda Peet, Jon Favreau, Paul Michael Glaser.
Director of photography, Michael Ballhaus ; editor, Joe Hutshing ; music, Hans Zimmer ; costume designer, Suzanne McCabe ; production designer, Jon Hutman ; visual effects supervisor, Scott Rader.
Originally released as a motion picture in 2003.
MPAA rating: PG-13; for sexual content, brief nudity and strong language.
Keywords: Man-woman relationships -- Drama; Myocardial infarction -- Drama; Physicians -- New York (State) -- East Hampton -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired